Effectiveness of adjuvant traditional Chinese medicine on macrovascular invasion in patients with hepatocellular carcinoma: a real-world propensity score-matched study - Yan, Huiwen; Wang, Xinhui; Yu, Lihua; Liu, Xiaoli; Yan, Fengna; Xie, Yuqing; Pu, Qing; Yang, Zhiyun (Frontiers in Pharmacology, 2024)
The study aimed to investigate the potential of traditional Chinese medicine (TCM) in reducing the risk of macrovascular invasion (MVI) in Chinese patients with hepatocellular carcinoma (HCC). This retrospective analysis involved 2,267 HCC patients treated at our hospital. Propensity score (PS) matching was used to compare TCM users (n = 485) with non-users (n = 485) in terms of age, Barcelona Clinic Liver Cancer (BCLC) staging, type of treatment, and AFP. The impact of TCM on the hazard ratio (HR) of MVI was evaluated using a Cox multivariate regression model. The efficacy of TCM therapy on MVI was further examined using the log-rank test. The analysis revealed that TCM medication was a significant protective factor for MVI in HCC patients, as evidenced by the Cox analysis (adjusted HR = 0.496, 95% CI: 0.387-0.635, p < 0.001). After PS matching, the Kaplan-Meier curve demonstrated a lower occurrence rate of MVI in TCM users compared to non-users. The study findings suggest that TCM treatment has the potential to decrease the incidence of MVI in HCC patients, irrespective of etiology, BCLC staging, liver function, or treatment type. Notably, as the use of TCM increased, the percentage of MVI in patients showed a gradual decrease, indicating the potential of TCM therapy as a successful strategy for preventing MVI.